Integration of Arabic Language Learning in the Formation of Social-Religious Identity in Madrasahs: A Systematic Study of Policy, Local Practices, and Digital Transformation - Ghufron, Zaki; Alawiyyah, Azizah; Kuakul, Yuttana (Al-Jadwa: Jurnal Studi Islam, 2025)
Arabic has an important position in the Islamic education system in Indonesia, not only as a means of religious communication, but also as a medium for shaping the social and religious identity of students. However, learning practices in madrasas, including in Banten Province, still face challenges in integrating spiritual, national, and linguistic values as mandated in KMA No. 183 of 2019. This study aims to systematically examine the role of Arabic language learning in shaping the social-religious identity of madrasah students in Banten using a Systematic Literature Review (SLR) approach. The analysis was conducted on the policies of the Ministry of Religious Affairs, reputable national and international scientific articles, and local research results published in the 2015–2025 period. The results of the study show that curriculum implementation is still dominated by a structural approach, lacks innovation, and is not yet fully contextual. However, the integration of local values and digital literacy has been proven to increase learning motivation, strengthen the sense of belonging, and build an inclusive and adaptive Indonesian-Muslim identity in the face of globalization. The contribution of this research lies in strengthening the theoretical and practical perspectives on Arabic language learning as a means of fostering religious-national character through the development of contextual curricula, improving teacher competence, and utilizing digital technology in madrasahs.